Tree Architecture Model and Tree Health Assessment Using Sonic 3D Tomograph Relationship in Bali Botanic Garden - Siti Fatimah Hanum; Ayyu Rahayu; Rajif Iryadi; I Dewa Putu Darma (Institut Pertanian Bogor (IPB University), 2023)
The incident of fallen trees or broken branches is dangerous for tourists visiting Bali Botanical Garden. Tree health monitoring in locations with high human activity and near valuable properties is mandatory to minimize the potency of tree failure. Since the stand stability is influenced by biological and physical factors, multiple variables consisting of species characteristics (stem form), tree dimensions (height, diameter, and slenderness coefficient), and tree health were used as parameters of tree health. The aim of this study is to examine the health condition of trees located in XIV.G Bali Botanical Garden and to identify the most significant morphological character related to the result of tomograph measurement. A purposive sampling technique was adopted for locations which highly visited. A total of 80 trees were examined as samples to measure tree health. The evaluation used visual observation and tomograph technology. The result showed the most tree defect found were branches covered with epiphyte and moss. However, tomograph examination found only one tree classified at high risk (Bischofia javanica) and seven trees classified at medium risk (Syzygium polyanthum, Syzygium racemosum, Bischofia javanica, Pittosporum mollucanum, Pittosporum sp. and Dacrycarpus imbricatus (2 trees)). This study suggests the use of tree architecture model as the most significant morphological character on tree samples with medium decay.